Subcontracting and rework cost sharing in engineering-procurement-construction projects - CHEN, Zhenzhen (Institutional Knowledge at Singapore Management University, 2023)
Infrastructure development projects are overwhelmingly managed through engineering–procurement–construction (EPC) contracts, which allow a project end user to shift all project risks to a contractor. Accordingly, the International Federation of Consulting Engineers recommended a contract template based on a lump-sum contract between the end user and main contractor. However, EPC projects often suffer from quality issues due to moral hazard, which is aggravated by the involvement of subcontractors hired by the main contractor to perform parts of the project. Besides, costly rework is frequently needed to achieve the contractually mandated quality. When the main contractor must share some of the subcontractor’s rework cost, an externality might arise. In this study, we model an EPC contract with three parties: the end user, the main contractor, and a representative subcontractor. We compare the end user’s cost and quality trade-off for the recommended lump-sum contract and the proposed incentive contracts. We find that the lump-sum contract can achieve the first-best trade-off under limited circumstances, whereas the appropriate incentive contract can do so for a wider range of circumstances. Rework cost sharing can cause under- or over-investment in efforts and reduce system welfare compared to the first-best outcome by weakening the incentive contract’s ability to overcome moral hazard. However, for a subcontractor with limited liability, rework cost sharing can improve project outcomes by allowing the main contractor to reduce the subcontractor’s risk exposure.